Інтегральнi рiвняння в загальнiй теорiї поглинання i розсiяння свiтла металевими нанокластерами - Tomchuk, P. M.; Starkov, V. M.; Butenko, D. V. (Publishing house "Academperiodika", 2018)
The problem of light absorption and scattering has been reduced to the solution of a singular integral equation for the complex vector of electric field intensity inside a nanoparticle. The dipole approximation is chosen as the initial one. The results of computing experiments testify to an acceptable agreement between the approach proposed for the consideration of the electric field inside a spherical nanoparticle and the results available for the optical and emission properties of metal nanoclusters.